Factors Affecting Coordination in Infrastructure Development of Kesumbo Ampai Village, Bathin Solapan District, Bengkalis Regency - Suherman; Novelma Lastri; Dwi Hartutik; Andi Desy Musdiana (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study was to determine the factors that influence coordination in infrastructure development in Kesumbo Ampai Village, Bathin Solapan District, Bengkalis Regency. The type of research conducted is qualitative research. Data collection using primary sources and secondary sources. The techniques used are observation, interviews, documents, for research informants, namely the District, Village Apparatus, BPD, Hamlet Head and RT. Data analysis in this research is qualitative data analysis according to Bogdan, namely the process of systematically searching and compiling data obtained from interviews, field notes, and other materials, so that it can be easily understood, and the findings can be conveyed. The results showed that there were factors that influenced coordination, namely the absence of socialization of the Vision and Mission of Kesumbo Ampai Village, operational standards had not been implemented optimally, low work discipline, the status of the Village Head who was still not definitive and development supervision was not optimal